The Kampo Medicine Rokumigan Possesses Antibiofilm, Anti-Inflammatory, and Wound Healing Properties. (30th April 2014) - Liao, James; Azelmat, Jabrane; Zhao, Lei; Yoshioka, Masami; Hinode, Daisuke; Grenier, Daniel
Abstract : Periodontal diseases, which are inflammatory diseases of bacterial origin affecting the tooth-supporting tissues, are characterized by inflammation and destruction of gingival connective tissue and alveolar bone, and may lead to tooth loss. The aim of the study was to investigate Rokumigan, a Kampo Japanese traditional medicine made of six different plants, for its capacity to prevent biofilm formation by Fusobacterium nucleatum, to inhibit interleukin-6 (IL-6) and interleukin-8 (IL-8) secretion by mucosal cells, and to promote wound healing in a fibroblast model. Using a microplate colorimetric assay, Rokumigan prevented biofilm formation by F. nucleatum, while it had no effect on bacterial growth. Rokumigan inhibited IL-6 secretion in both epithelial cells and fibroblasts stimulated with lipopolysaccharide. However, it caused no significant inhibition of IL-8 secretion by both cell types. Rokumigan significantly increased proliferation and migration of gingival fibroblasts in a wound healing assay. In conclusion, the Kampo formulation Rokumigan, through suppression of biofilm formation by F. nucleatum, inhibition of IL-6 secretion by gingival epithelial cells and fibroblasts, and promotion of wound healing in a fibroblast model, may have potential application for periodontal diseases.